Becoming socialized in a COVID-19 World: A survey exploring the response of regional Australians’ health-related behavior patterns - Jodie Kleinschafer; Jessica Kingsford; Julaine Allan (Health Literacy and Communication Open)
Consumer socialization theory provides a means of understanding how adults drew on the expert knowledge of socialization agents to develop the skills, knowledge, and attitudes required to function in a COVID-19 world. In this paper, we report on a project conducted in partnership with two universities, a local health district and First Nations researchers to understand the role of socialization agents in supporting the community response to the threat of COVID-19. A quantitative survey was conducted of 701 individuals in rural, regional and remote New South Wales (NSW), Australia. The socialization agents they used could be categorized into four types (Government, Professional, Personal, and Mass Media). The community could be segmented based on the types of socialization agents they used, and there was a significant difference across the segments in terms of their behavioral intentions and their adoption of preventative health behaviors, such as wearing masks and social distancing. The results point to the need to leverage the role of socialization agents during social change and to use targeted health-based promotion.